Experimental evidence for fractionation of tin chlorides by redox and vapor mechanisms. (1st April 2019) - Wang, Da; Mathur, Ryan; Powell, Wayne; Godfrey, Linda; Zheng, Youye
Abstract: Multiple mechanisms have been proposed to induce fractionation of tin in ores and rocks. Experimental evidence to support and characterize the causes for fractionation is lacking. Here, we present laboratory vapor-induced and redox-driven experiments to resolve the directionality and relative magnitude of fractionation caused by these geologically prominent mechanisms. Vapor-induced fractionation without redox reactions at 150 °C resulted in the residual solution becoming isotopically lighter by 0.15‰ (δ 124 Sn with all values reported in comparison to NIST 3161A). Tin chloride solutions that were electrolytically reduced to form metal produced residual solutions that were 0.40‰ heavier (δ 124 Sn). The reduced metal from these experiments was lighter than the solutions and starting materials. These experiments confirm that heavier tin isotopes are favored in a stronger bonding environment associated with oxidation, and that the vapor favors heavier tin in SnCl4 . Empirical confirmation of the magnitudes and directions of tin isotope fractionation determined through experimentation are evident in the comparison of the isotopic composition of cassiterite ores from contrasting mineralizing environments. Pegmatites and associated greisen ores that formed deep within the Earth, and so experienced redox reactions without vapor partitioning (Etta, South Dakota; Elsmore, New South Wales) display a variation of only 0.8‰ (δ 124 Sn). In contrast, cassiterite that formed from vapor-rich fluids in volcanic to subvolcanic environments, and so experienced both redox and vapor fractionation mechanisms (Taylor Creek, New Mexico, Durango, Mexico; Potosi and Oruro, Bolivia) display a much larger range of cassiterite values, of up to 2‰ (δ 124 Sn). It is likely that tin isotope fractionation via these mechanisms contribute to the observed variations in igneous rocks.